Factors associated with academic underachievement: a cross-sectional study in Atacora Northern Benin republic - Assogba, Omonlola K. Elvire; Madodé, Yann Eméric; Francisco, Anelia Merveille Ebilola; Kossou, Jahdiel; Lokonon, Jaurès; Luginaah, Isaac; Amoussa Hounkpatin, Waliou (Frontiers in Education, 2025)
AimThis study aimed to identify factors associated with low academic performance among public primary pupils in Atacora Department, Benin Republic.MethodsThis cross-sectional study is conducted among pupils aged 8–14 years from public primary schools. Data on dietary diversity were collected using a 24-h dietary recall tool adapted from the FAO guidelines. Nutritional status was assessed through anthropometric measures and hemoglobin level, while cognitive abilities were assessed using Digit Span and Verbal fluency tests. The socio-economic, demographic and health characteristics were collected through digitalized questionnaires administered to pupils. Physical activity levels were measured using the Physical Activity Questionnaire for children (PAQ-C) Form. Academic performance was measured using end-of-month examination results provided by school boards.Resultsfindings revealed that almost half (46.34%) of the pupils scored less than 10 out of 20 and were in fail category. Among pupils with normal growth according to WHO standards, cognitive factors as low Verbal fluency (OR = 3.119, p < 0.05); low Digit span (OR = 2.623, p < 0.05); nutritional factors as low dietary diversity (OR = 2.283, p < 0.05); socioeconomic conditions including paternal illiteracy (OR = 1.422, p < 0.05), and lack of household electricity (OR = 2.009, p < 0.05), and school related factors as long distance to school (OR = 3.187, p < 0.05), high level of absenteeism (OR = 1.052, p < 0.05), are predictors of academic underachievement.ConclusionOverall, Cognition, dietary diversity, access to electricity, pupils’ gender, distance to school, father’s literacy, are predictors of school performance in the study area. Integrated, context-sensitive policy interventions—spanning early childhood education, rural electrification, gender equity, parental engagement, school attendance, teacher training, nutritional support, and improved food accessibility—are crucial for enhancing academic performance in food-insecure regions of Northern Benin.